Implementasi Problem Based Learning Untuk Meningkatkan Kemampuan Berpikir Kritis dan Hasil Belajar Siswa Pada Pembelajaran IPS SD - Aan Saputri; Suardi Suardi; Syarifah Aeni Rahman (Departement of Mathematics Education, 2024)
The main problem in this research is how to apply the Problem Based Learning learning model to improve students' critical thinking skills and learning outcomes in social studies subjects and how to improve students' critical thinking skills and learning outcomes through the application of the Problem Based Learning learning model in social studies subjects for fifth grade elementary school. Borongkanang State District. Bontonompo, Gowa Regency. This research aims to determine the implementation of the Problem Based Learning learning model to improve critical thinking skills and student learning outcomes in social studies subjects and to determine the increase in critical thinking skills and student learning outcomes through the implementation of the Problem Based Learning learning model in social studies subjects in class V of State Elementary Schools. Borongkanang Kec. Bontonompo Kab. Gowa. This type of research is classroom action research (Class Action Research) which is carried out in two cycles where each cycle is carried out in four meetings. Research procedures include planning, implementation, observation and reflection. The subjects in this research were 27 class V students. The results of the research are based on the social studies subject evaluation test of students in the first cycle who reached the KKM. Of the 27 students, there were 11 people with a percentage of 41%, while there were 16 people who had not reached the KKM with a percentage of 59% with an average score of 61. Meanwhile, in the second cycle there was an increase in students. Of the 27 people who reached the KKM, there were 19 people with a percentage of 70% and those who did not meet the KKM were the remaining 8 people with a percentage of 30%. The average score of students in cycle II was 75. The critical thinking skills and student learning outcomes are based on indicators of critical thinking skills and Learning outcomes have increased as evidenced by the fact that in cycle I a score of 31 was obtained with a percentage of 64%, while in cycle II a score of 43 was obtained with a percentage of 89%.